Treatment Options for Relapsed Acute Lymphoblastic Leukemia Study - Ishfaq Ahmad, Anwar Ullah, Amir Muhammad (Pakistan Journal of Medical & Health Sciences, 2023)
This study aims to analyze the treatment options for relapsed acute lymphoblastic leukemia (ALL). ALL is a type of cancer that affects the white blood cells, and can often recur after initial treatment. The focus of this study is to evaluate the efficacy of various treatments for relapsed ALL, including chemotherapy, radiation therapy, bone marrow transplantation, and targeted therapies. Results from a systematic review of the literature indicate that treatment options for relapsed ALL are often effective, but can vary depending on the stage of the disease. Chemotherapy and radiation therapy are typically used as first-line treatments, while bone marrow transplantation is typically used as a second-line treatment. Targeted therapies, such as monoclonal antibodies, are increasingly being used in combination with other treatments. This study suggests that further research is needed to determine the optimal treatment strategy for relapsed ALL, as well as the best combination of treatments. Objectives: To investigate the current treatments for relapsed acute lymphoblastic leukemia (ALL) Methodology: This study conducted in department of pediatric Hematology and oncology CMH Rawalpindi From jan 2020 to jan 2023 Comprised 100 pediatric patients with relapsed ALL. Patients were treated with chemotherapy, radiation therapy, stem cell transplantation, or targeted therapy. The efficacy of each treatment option was assessed by the complete remission rate, overall survival rate, and relapse rate. The complete remission rate was determined by measuring the number of patients who achieved complete remission after eight weeks of treatment. The overall survival rate was measured by calculating the number of patients who survived at least one year following treatment. Finally, the relapse rate was calculated by determining the number of patients who experienced recurrence of the disease within one year. Data was collected and analyzed using descriptive statistics and survival analysis. Results The results of this study showed that chemotherapy was the most effective treatment option, with a complete remission rate of 60%, followed by stem cell transplantation (50%) and targeted therapy (40%). The overall survival rate was highest in the chemotherapy group (72%), followed by the stem cell transplantation (53%) and targeted therapy (48%) groups. Radiation therapy was found to be less effective, with a complete remission rate of only 25%. The relapse rate was highest in the targeted therapy group (30%), followed by the stem cell transplantation (20%) and chemotherapy (15%) groups. Conclusion: This study showed that chemotherapy was the most effective treatment option for relapsed pediatric ALL, followed by stem cell transplantation and targeted therapy. The overall survival rate was highest in the chemotherapy group, followed by the stem cell transplantation and targeted therapy groups. Radiation therapy was found to be less effective, with a complete remission rate of only 25%. These results suggest that chemotherapy should be the primary treatment option for relapsed pediatric ALL, followed by stem cell transplantation and targeted therapy as secondary options. Keywords: acute lymphoblastic leukemia, relapsed, chemotherapy, radiation therapy, stem cell transplantation, targeted therapy